2008
DOI: 10.1063/1.2831362
|View full text |Cite
|
Sign up to set email alerts
|

Electrical, structural, and chemical properties of semiconducting metal oxide nanofiber yarns

Abstract: The electrical, structural, and chemical properties of twisted yarns of metal-oxide nanofibers, fabricated using a modified electrospinning technique, are investigated in this report. In particular, synthesized zinc oxide and nickel oxide yarns having diameters in the range of 4-40 m and lengths up to 10 cm were characterized, whose constituent nanofibers had average diameters of 60-100 nm. These yarns have one macroscopic dimension for handling while retaining some of the properties of nanofibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 15 publications
(14 reference statements)
0
26
0
Order By: Relevance
“…In this approach, colloidal dispersions of nanosized charged particles are set into an oriented motion by the application of an external electric field. [133][134][135] The use of electrospinning was demonstrated for the production of Co, [136] Mn, [137] Fe, [138] In, [139] Ti, [140] Zr, [141] Ni, [142] and Zn [143] oxide NWs. [43] Polycrystalline oxides are typically obtained by electrophoretic deposition, [93][94][95] although the possibility of growing single-crystal nanostructures with processes assisted by mild annealing was also demonstrated.…”
Section: Synthesis Of Metal Oxide Nanowires and Nanorodsmentioning
confidence: 99%
“…In this approach, colloidal dispersions of nanosized charged particles are set into an oriented motion by the application of an external electric field. [133][134][135] The use of electrospinning was demonstrated for the production of Co, [136] Mn, [137] Fe, [138] In, [139] Ti, [140] Zr, [141] Ni, [142] and Zn [143] oxide NWs. [43] Polycrystalline oxides are typically obtained by electrophoretic deposition, [93][94][95] although the possibility of growing single-crystal nanostructures with processes assisted by mild annealing was also demonstrated.…”
Section: Synthesis Of Metal Oxide Nanowires and Nanorodsmentioning
confidence: 99%
“…The ropes show sensitivity 4.5% at a NH 3 concentration of 1000 ppm. Metal oxide microyarns, in particular, consisting of nanofibers or nanotubes prepared using electrospinning [19,25], may not be fabricated in this manner because nanotube forests are required but are not readily prepared. Lotus et al [25] reported metal oxide nanofiber yarns.…”
Section: Introductionmentioning
confidence: 98%
“…Metal oxide microyarns, in particular, consisting of nanofibers or nanotubes prepared using electrospinning [19,25], may not be fabricated in this manner because nanotube forests are required but are not readily prepared. Lotus et al [25] reported metal oxide nanofiber yarns. They first prepared nanofibers by electrospinning polymer solution containing metal oxide precursor, then aligned and twisted them into microyarns.…”
Section: Introductionmentioning
confidence: 98%
“…13 Zinc oxide can be synthesized by various techniques including hydrothermal synthesis, 14 electro deposition, arc discharge method, 15 wet chemical methods, thermal decomposition method, 16 sol-gel methods, vacuum evaporation, 17 direct precipitation, 18 RF plasma synthesis, 19 and electrospinning techniques. 21 It is the most versatile and simple technique for the synthesis of ZnO nanofibers due to its greater efficiency and low cost. 21 It is the most versatile and simple technique for the synthesis of ZnO nanofibers due to its greater efficiency and low cost.…”
Section: Introductionmentioning
confidence: 99%